Model Internalisasi Nilai-nilai Multikultural dalam Pembelajaran PAI di SMA Negeri 1 Nganjuk - Arifin , Zainal; Masyukuri , Masyukuri; Hanif , Moh. (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
This study uses a qualitative approach with a type of case study that focuses on cultivating multicultural values ​​that are contained in the learning process inside and outside the class of SMA Negeri 1 Nganjuk. The purpose of this study is to reveal and develop a model of internalization of multicultural values ​​that grows and develops in the research locus. Sources of data related to this study were obtained using in-depth interview techniques, participatory observation and documentation which were processed using the interactive model of Miles and Huberman. From this focus, a multicultural value internalization model was produced through the management of systematic and coordinated learning as well as habituation and training in developing student character.